PENDIDIKAN KESEHATAN TENTANG ROM MENINGKATKAN MOTIVASI KELUARGA DALAM MELAKUKAN RANGE OF MOTION (ROM) PADA PASIEN STROKE INFARK DI IRNA SERUNI A RSUD Dr. SOETOMO SURABAYA - Sunaryo Sunaryo; Elida Ulfiana; Deni Yasmara (Universitas Airlangga, 2019)
Introduction: Stroke is a disease that needs attention, especially for patients and their families. Not all families have the motivation to do a ROM for various reason. The aimed of this study was to examine the influence of health education to the family motivation to do ROM for the patients with infarction stroke in Seruni A Ward, Dr.Soetomo Hospital Surabaya.Methods: This study was used Pre Experimental Design. Population in this study were all family of the patients with infarction stroke in Seruni A Ward, Dr.Soetomo Hospital Surabaya. Purposive sampling technique was used in this study. There were 10 respondents as the sample who met to the inclusion criteria. The independent variable was helath education about Range Of Motion (ROM) and the dependent variable was the patient's family motivation to do ROM. Data were collected and analyzed using Wilcoxon Signed Ranks test.Results: The results showed that there was an effect of health education to family motivation to do ROM for the patients with infarction stroke in Seruni A Ward, Dr.Soetomo Hospital Surabaya (p=0.01).Conclusions: Health education about the ROM influence family motivation in carrying out physiotherapy. Nurses and other health professionals should provide health education in order to motivate families to increase and accelerate the healing process of patients. The results of this study can be further investigated by comparing the extension method, which one is more effective to motivate patients and it can associated with a cure rate of patients.